Pengaruh Keseimbangan Kehidupan Kerja Terhadap Perilaku Kewargaan Organisasi Melalui Komitmen Organisasi Pada Guru SMK Swasta di Jakarta Timur - Anindia Ningtias Saputri; widya parimita; Rizki Firdausi Rachmadania (Publikasi Indonesia, 2023)
School is a service organization that carries out the teaching and learning process. Schools must develop organizational citizenship attitudes and behaviors as additional (voluntary) behaviors outside of formal job requirements that provide benefits to schools and can continue to develop and achieve the goals set. The success of education is inseparable from the success of educators, one of which is the teacher. The quality of teachers is a driving force in producing superior, character and quality individuals. The research was conducted to see the effect of work-life balance on organizational citizenship behavior through organizational committees of private vocational school teachers in East Jakarta. The method used in this research is descriptive quantitative method, with a survey approach. The results showed that there was a significant and positive direct effect between work-life balance on organizational citizenship behavior, a significant and positive direct effect between work-life balance on organizational commitment, a significant and positive direct effect between organizational commitment on organizational citizenship behavior, and there is a significant and positive indirect effect between work-life balance on organizational citizenship behavior mediated by organizational commitment.